Digital Citizenship Capabilities Among Indigenous Senior High School Students: A Multidimensional Analysis in Resource-Constrained Contexts - Gopeng, Wisdom Reeves; Dulay, Michele (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examines digital citizenship education (DCE) capabilities among indigenous senior high school students in Tinoc, Ifugao, Philippines, with the aim of identifying capability gaps and informing context-responsive educational transformations. Grounded in Sen’s Capability Approach, Sociotechnical Systems Theory, and Indigenous Knowledge Systems, the research adopts a quantitative descriptive design within a post-positivist framework. Data were collected from 211 students using a validated 58-item survey instrument measuring eight DCE dimensions: knowledge, skills, attitudes, literacy, behavior, safety, digital footprints, and ethics. Descriptive statistics and independent samples t-tests were employed to analyze overall profiles and demographic differences. Findings reveal a “foundational but fragmented” DCE profile (M = 3.12), where affective-behavioral dimensions (attitudes, behavior, safety, ethics) outperform cognitive-capability dimensions (knowledge, skills, literacy, footprints). Significant deficiencies were observed in digital footprints (M = 2.69) and source evaluation (M = 2.83), indicating limited critical digital agency. A notable knowledge–attitude gap (0.24) suggests “false competency,” while structural factors such as device ownership significantly influence capability development. Gender differences favor females in skills, literacy, and safety, and internet access primarily affects attitudes and behavior rather than cognitive competencies. The study concludes that DCE in resource-constrained indigenous contexts promotes protective rather than empowered citizenship. It recommends pedagogical reforms emphasizing critical literacy, technical resilience, and culturally grounded participation through indigenous governance principles such as Keleng. This research supports Sustainable Development Goal (SDG) 4.7 by addressing global citizenship and digital literacy competencies in marginalized contexts. Its sustainability impact lies in strengthening equitable, culturally responsive education systems that enhance community-based digital participation and reduce structural inequalities in rural education settings.